ChemInform Abstract: Strepoxazine A, a New Cytotoxic Phenoxazin from the Marine Sponge‐Derived Bacterium Streptomyces sp. SBT345. Issue 52 (6th December 2016) - Cheng, Cheng; Othman, Eman M.; Fekete, Agnes; Krischke, Markus; Stopper, Helga; Edrada‐Ebel, RuAngelie; Mueller, Martin J.; Hentschel, Ute; Abdelmohsen, Usama Ramadan
Abstract: Strepoxazine A (I) exhibits cytotoxic activity against leukemia HL‐60 cells.